When Text Collaborates with Violence Language and Sexual Violence in Social Media in Indonesia Gender and Sexuality Ideologies - Rahmat, Wahyudi; Samsiarni, Samsiarni; Willia, Angge; Putri, Adela Primadona; Rusdi, Fischa Rina (Journal of Humanity Studies, 2023)
This article explores the complexity of the relationship between language and sexual violence in the context of social media in Indonesia. This research investigates gender and sexuality ideologies that permeate digital texts, creating space for the normalization and spread of sexual violence. Through in-depth analysis of various social media platforms, this article explores the impact of language on society's views on gender and sexuality, raising critical questions about the urgency of preventive and educational action to combat sexual violence in the digital realm.